LOCATION DESIGN FOR EMERGENCY MEDICAL CENTERS BASED ON CATEGORY OF TREATABLE MEDICAL DISEASES AND CENTER CAPABILITY - Ko, Young Dae (International Journal of Industrial Engineering: Theory, Applications and Practice, 2014)
<span lang="EN-US" style="color: black; font-family: "Times New Roman","serif"; font-size: 10pt; mso-fareast-font-family: 바탕; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">Through the development of a mathematical model, this paper studies the location design of emergency medical centers in a given region under the closest assignment rule. It is assumed that the capability and capacity to treat various categories of treatable medical diseases are provided for each candidate medical center. Once a candidate center is selected, it will receive subsidies from the government to support the offering of medical services at a competitive cost. It is further assumed that the number of patients occurring at each patient group node during a unit time is known along with the categories of their diseases. With the objective of minimizing the total subsidies paid, we select from among the candidate emergency medical centers subject to a maximum total budget and minimum desired survival rate constraints. The problem is formulated as an integer program (IP) and the CPLEX version 12.1 solver is used to obtain an optimal solution. A genetic algorithm is developed to obtain good feasible solutions much more quickly than is possible via CPLEX. Simulation studies are conducted to evaluate the performance of the proposed deterministic models in a stochastic context.